Possible effects of obesity on motor development, executive functioning, and academic performance of schoolchildren from a neuropsychopedagogical perspective - Cardoso, Fabricio Bruno; Loureiro, Vitor da Silva; Batista, Washington Adolfo; Bonone, Filipe Meneghelli; Carvalho, Aliny dos Santos; Lima, Alisson Padilha de; Esteves, Joao Vitor Galo; Sholl-Franco, Alfred (Nurture, 2023)
Purpose: This study aimed to compare the motor competence, executive functioning, and academic performance of students with adequate weight, overweight, and obesity. Design/Methodology/Approach: A total of 1631 children aged between 06 and 08 (±7.58) years old, of both genders (903 girls and 728 boys), students of the public school system in the state of Rio de Janeiro, participated in this study. To achieve the objective, participants were introduced to protocols that assessed body mass index, Motor Competence, Executive Functioning, Reading Comprehension, and Academic Performance. Findings: When analyzing the results of the protocols related to motor development, cognitive development, and academic performance, the results show a superiority of children with weights within the expected range in relation to obese children. Conclusion: The findings indicate a potential correlation between body mass index (BMI) and the proficiency of children in motor skills, executive functions, and academic performance. Specifically, the results demonstrate that children who are obese exhibit lower scores in all assessed variables compared to children with a BMI within the normal range. Research Limitations and Implications: This study did not assess the participants level of physical activity or their eating habits. Practical Implications: The research results contribute to the formulation of public policies on obesity as a public health problem, since its impacts go far beyond physical health problems. Contribution to the Literature: This research can add to the literature on the impacts of obesity on the cognitive and motor development of children, showing the importance of developing new studies with regard to prevention.